Agents of trustees? International courts in their political context - Karen J. Alter (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2004)
Principal-Agent (P-A) theory sees the fact of delegation as defining a relationship be-tween states (collective Principals) and international organizations (Agents) with recon-tracting threats being the predominate way states influence IOs. Developing a category of Trustee-Agents, I argue that recontracting tools will be both harder to use and less effective at influencing the Trustee-Agents. Trustee-Agents are 1) selected because of their personal reputation or professional norms, 2) given independent authority to make decisions according to their best judgement or professional criteria, and 3) empowered to act on behalf of a beneficiary. Focusing on state-International Courts (IC) relations, the article develops an alternative explanation that highlights the need for international judges to balance legal fidelity with the significant international challenge of endeav-ouring compliance. The arguments are explored through three case studies of IC deci-sion-making that call into question the 'rational expectations' claim that ICs are tailor-ing their decisions to reflect the wishes of powerful states and avoid adverse recontracting.
Keywords: 330; Treuhänder; Internationale Gerichtsbarkeit; Theorie; Internationales Recht; Agency Theory